2017
DOI: 10.1128/iai.00930-16
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Regulators Are Required for Metabolic Fitness in Vibrio parahaemolyticus

Abstract: Quorum sensing (QS) is a process by which bacteria alter gene expression in response to cell density changes. In Vibrio species, at low cell density, the sigma 54-dependent response regulator LuxO is active and regulates the two QS master regulators AphA, which is induced, and OpaR, which is repressed. At high cell density the opposite occurs: LuxO is inactive, and therefore OpaR is induced while AphA is repressed. In Vibrio parahaemolyticus, a significant enteric pathogen of humans, the roles of these regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 89 publications
1
46
0
1
Order By: Relevance
“…A ΔluxO mutant exhibits significant fitness defects, while an ΔopaR mutant shows fitness advantages when grown on a variety of different carbon sources (e.g., glucose, gluconate, mannose, ribose, and arabinose). These results suggest that OpaR balances metabolic flux in V. parahaemolyticus in a manner similar to HapR in V. cholerae (99).…”
Section: Luxr/hapr Regulation Of Group Behaviors In Vibriosmentioning
confidence: 51%
See 1 more Smart Citation
“…A ΔluxO mutant exhibits significant fitness defects, while an ΔopaR mutant shows fitness advantages when grown on a variety of different carbon sources (e.g., glucose, gluconate, mannose, ribose, and arabinose). These results suggest that OpaR balances metabolic flux in V. parahaemolyticus in a manner similar to HapR in V. cholerae (99).…”
Section: Luxr/hapr Regulation Of Group Behaviors In Vibriosmentioning
confidence: 51%
“…Quorum sensing via LitR activates the production of acetyl coenzyme A (acetyl-CoA) synthase (Acs), which converts acetate into acetyl-CoA and counteracts the acidification (98). In addition, the quorum sensing network in V. parahaemolyticus represses 64 genes associated with the transport and metabolism of amino acids, carbohydrates, and lipids (99). A ΔluxO mutant exhibits significant fitness defects, while an ΔopaR mutant shows fitness advantages when grown on a variety of different carbon sources (e.g., glucose, gluconate, mannose, ribose, and arabinose).…”
Section: Luxr/hapr Regulation Of Group Behaviors In Vibriosmentioning
confidence: 99%
“…Quorum sensing is a form of bacterial communication used to coordinate behaviors in response to changing cell density. The quorum sensing circuitry has been studied extensively in V. harveyi, and a similar system with a LuxR homologue, OpaR, has been demonstrated in V. parahaemolyticus (16)(17)(18)(19)(20)(21)(22). Quorum sensing involves the synthesis of autoinducers (AIs), which bind to receptors, triggering a phosphorelay pathway that activates LuxO, the master response regulator.…”
mentioning
confidence: 99%
“…Previously, it was shown that LuxR in V. harveyi positively regulates glycine betaine biosynthesis genes (32). In V. parahaemolyticus, it was demonstrated that the ectoine biosynthesis genes were repressed in a luxO mutant (where OpaR levels are high) compared to the wild type (WT) (22).…”
mentioning
confidence: 99%
“…Previous studies have shown that Vibrio species can utilize intestinal mucus as a carbon and energy source (25)(26)(27)(28). Therefore, we examined the expression pattern of the ula genes in V. cholerae cells growth in M9-Mucus.…”
Section: Resultsmentioning
confidence: 99%